ECONOMIC EMPOWERMENT OF WOMEN: A REVIEW OF CURRENT RESEARCH - Irshad Ahmad Reshi; Dr T. Sudha (RADJA PUBLIKA, 2023)
Abstract Economic empowerment of women has gained increasing attention as a key factor for promoting gender equality and sustainable development. This research article provides a review of the current literature on economic empowerment of women, focusing on the main strategies, challenges, and impacts of interventions aimed at promoting women's economic empowerment. The review draws on a wide range of studies from different regions and sectors, including microfinance, entrepreneurship, vocational training, and employment policies. The article highlights the need for a more integrated and comprehensive approach to women's economic empowerment that addresses the structural barriers to women's full participation in the economy.